Breaking the Frame: Arabesque and Metric Complexity in the Sunrise Scene from Ravel’s Daphnis et Chloé (1912) - Gurminder Kaur Bhogal (Zeitschrift der Gesellschaft für Musiktheorie)
The arabesque is a type of ornament that achieved considerable popularity during the Art Nouveau movement of the fin/debut-de-siècle. This paper examines how in the Sunrise Scene from Ravel’s ballet, Daphnis et Chloé (1912), he conceived of this ornament as an ostinato motif whose short rhythmic values trace the “S-curve” of contemporaneous visual arabesque through a periodic descending and ascending melodic contour. This undulating figure’s initial characterization as an inconsequential decoration betrays its growing significance as a metric, formal, and narrative catalyst. I show how its constant presence, yet fluctuating prominence, brings into central view shifting metric irregularities and conflicts, which I explore using theoretical models developed by Harald Krebs and Richard Cohn. By incessantly coming in and out of auditory focus, one never knows whether this motif is a background accompaniment or something more substantial until a significant narrative juncture: Daphnis’s awakening after a long, anxious slumber. At this moment, the motif bursts into the foreground to suggest the symbolic fusion of nature, divinity, and human emotion. The structural role of the arabesque figure on metric and narrative levels unsettles prevailing viewpoints of ornament as meaningless and non-essential. In so doing, this gesture indicates Ravel’s vibrant conception of the metric hierarchy and its inter-relationships, while promoting a vital convergence of meter, musical form, and drama.